Pemetaan dan strategi peningkatan kinerja Lembaga Pelayanan Perizinan Daerah dengan metode MBNQA-SWOT - Hafidz Anggara; Sawarni Hasibuan (Universitas Mercu Buana, 2020)
In order to realize bureaucracy reform of public service, especially licensing service and easy doing of business in Indonesia need to be done planning improvement strategy of regional Licensing service. Gap performance analysis regional licensing service board of DKI Jakarta conducted using MBNQA method with criteria MBCfPE version 2017-2018, while the design of the performance improvement strategy of the board of regional licensing services of DKI Jakarta is done with SWOT analysis. The results of the performance measurement of regional licensing service of DKI Jakarta using MBNQA standard resulted in a score of 752,475 which is at the level of an excellent global image with industry leader category. SWOT analysis results put the regional licensing service of DKI Jakarta in the Quadrant I (strengths-opportunities) that recommend the strategy of aggressive. Researchers recommend ten strategies for the performance improvement of the Regional Licensing Service Board of DKI Jakarta.